How Does Foreign Aid Affect the Relationship between IFRS Adoption and Foreign Direct Investment? - Efobi Uchenna; Matthias Nnadi (African Governance and Development Institute (AGDI), 2015)
This paper constructs a theoretical model to explain the relationship between IFRS adoption, FDI and foreign aid. Using the SGMM estimation technique to check the issue of endogene-ity and reverse causality, this relationship was examined on 92 countries for the period 2003-2012. Overall, IFRS adoption attracts more aid when conditioned on foreign aid; however, when disaggregating foreign aid, the effect of foreign aid on the nexus was contradictory, while multilateral aid flow was positive. This result remained consistent despite the battery of checks.
Keywords: 330; Accounting Standards; Foreign Aid; Foreign Direct Investment; Globalisation; IFRS Adoption